Structural Access and Relational Reinforcement in Community-Based Alternative Education: A Naturalistic Study of a PKBM–Church Partnership in Indonesia - Manurung, Ruth Sahanaya; Ayub, Daeng; Jais, Muhammad (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2026)
Abstract: Community learning centers can extend educational access, but less is known about how partnerships with faith-based organizations shape institutional access and everyday learning interactions. This naturalistic qualitative study examined collaboration between PKBM Bina Kreasi and an Adventist church institution in Tuah Karya, Pekanbaru, Indonesia. Data comprised interviews with three key program informants, observations conducted on 10 and 13 August 2025, and review of curriculum, administrative, instructional, and faith-based documents. Evidence was organized within four domains—positive behavior, verbal response, nonverbal response, and motivational support—and compared across interviews, observations, and documents. The analysis indicates two complementary layers of educational strengthening. First, PKBM Bina Kreasi provided structural access through curriculum, academic administration, learning materials, reporting processes, and a pathway to recognized credentials, while the church contributed a local venue, volunteer tutors, moral mentoring, and social support. Second, tutors generated relational reinforcement through respectful dialogue, specific encouragement, eye contact, smiles, responsive explanations, appropriate challenges, simple rewards, and personal attention. These practices coincided in the observed setting with participation, task responsibility, orderly behavior, courteous communication, and sustained motivation. The evidence also revealed variability: some learners were shy, fatigued, distracted, bored, or constrained by family work obligations and stigma toward non-formal education. The study therefore does not establish causal effects on academic achievement. It contributes an empirically grounded distinction between structural access and relational reinforcement and shows how their interaction may support an inclusive learning climate. Comparative, longitudinal, and learner-centered research is needed to test the transferability and outcomes of this model.